Seismic Damage Assessment of an 891 Years Old Historic Masonry Mosque - Karaton, Muhammet; Aksoy, Huseyin Suha (Budapest Univ Technology Economics, 2018)
Diyarbakir Grand Mosque is one of the oldest and the most significant mosques in the Islamic world and the Mesopotamia. The mosque was heavily damaged due to fire following an earthquake which was predicted 8 magnitude in 1114. It was rebuilt between 1117 and 1125. It is predicted that a great earthquake in the forthcoming years will be occurred in the region. Therefore, conservation and retrofitting works should execute for this 891 years old building. In this study, nonlinear seismic analyses of the main prayer hall of the mosque are performed and damage assessment of it due to a probable great earthquake is determined. Material properties of the mosque are defined by using nondestructive tests. Three level seismic acceleration data are produced by considering seismic characteristics of the region. Damage regions on the mosque are obtained under these earthquake loads. Suggestions about retrofitting of this significant historical mosque are recommended.
Keywords: Diyarbakir Grand Mosque; Sseismic characteristics; nondestructive tests; propagations of damages; conservation work